I'd Like to Pay with Your Visa Card : An Illustration of Illicit Online Trading Activity in the Underground Economy - Vömel, Stefan; Holz, Thorsten; Freiling, Felix (2010)
With the growing use and financial importance of the Internet, cyber criminals increasingly perceive computer systems, network architectures, and databases storing transaction- and personal-related data as assets and profitable targets. As illicit activities have become more organized and monetary-driven, a digital underground economy for hacking-related goods and services has evolved. In this paper, we outline the infrastructure and modes of operation of said economy with the help of real world samples captured in a communication channel on an IRC network. Thereby, we are able to gain a better understanding of the dynamics and interactions on this market. <br
UnivIS-Import:2016-06-30:Pub.2010.tech.IMMD.lehrst.idlike
Keywords: honeypot; honeynet; underground economy; cyber crime; IRC